Performance of recycled aggregate concrete composite metal decks under elevated temperatures: a comprehensive review - Fetih Kefyalew; Thanongsak Imjai; Reyes Garcia; Nguyen Khanh Son; Sandeep Chaudhary (Journal of Asian Architecture and Building Engineering, 2025)
This comprehensive review explores the performance of composite metal decks and structural elements incorporating recycled aggregate concrete (RAC) at elevated temperatures. Despite the acknowledged environmental benefits of using recycled aggregates in concrete production, there is a notable gap in the literature regarding their behaviour under fire conditions. The investigation delves into studies encompassing fire resistance, physio-thermal properties, mechanical attributes, and structural performance of composite metal decks constructed with RAC. The analysis reveals that the inclusion of recycled aggregates has both positive and negative impacts on these elements when exposed to high temperatures. The fire resistance of metal decking composite slabs is significantly influenced by material properties, composition, and RAC mix design. Experimental findings indicate that RAC slabs showed larger midspan deflection under load and fire exposure compared to their counterpart NC slabs. After 120 min. of duration, the mid-span deflection of RAC-0 was recorded to be 19 % higher than the corresponding deflection of NC-0 slab. While temperature-time curves show comparable performance between RAC and natural concrete (NC) slabs, RAC slabs exhibit a notably lower ratio of soffit temperature to the upper surface temperature, resulting in increased spalling. In conclusion, this study advocates for the broader utilization of RAC in constructing structural elements, particularly composite slabs facing extreme temperatures. However, it emphasizes the need for additional research to optimize fire resistance and gain a comprehensive understanding of their behaviour. The findings provide essential guidance for structural engineers and researchers involved in the design of sustainable and fire-resistant structures.